Linear analysis of micromorphic thermoelastic materials with microtemperatures and triple porosity - Kansal Tarun (Theoretical and Applied Mechanics)
This paper seeks to establish the fundamental equations governing anisotropic micromorphic thermoelastic media with triple porosity and microtemperatures. The proposed model takes into account the influences of porosity and microtemperatures, both of which play significant roles in accurately capturing the behavior of specific materials. Additionally, the objective of the paper is to develop a fundamental solution for the system of equations under steady, pseudo-static, quasi-static oscillations, and equilibrium conditions.